2003
DOI: 10.1046/j.1365-2214.2003.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

An observational study investigating the health provision for children with epilepsy within secondary schools in the East Midlands, UK

Abstract: Schools rely heavily on obtaining medical information from non-medical sources. Individual health care plans for children with epilepsy are not commonly undertaken. Few children had any restriction or special provision placed upon them because of their epilepsy except in the area of computer use. Further action is needed to consider how the system for providing for such children can be improved so that each child's individual health needs can be satisfactorily met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
5
1
1
Order By: Relevance
“…The interpersonal dimension refers mainly to behaviors that are observable, such as relationships with peers, ability to form friendships, as well as aggressive behavior. 27 , 28 Therefore a high correspondence on this dimension is not surprising. 29 On the other hand, the Future Worries dimension is not as accessible or directly observable, since it refers to worries expressed by the child over the future ( e.g ., not being able to drive a car when they grow up).…”
Section: Discussionmentioning
confidence: 95%
“…The interpersonal dimension refers mainly to behaviors that are observable, such as relationships with peers, ability to form friendships, as well as aggressive behavior. 27 , 28 Therefore a high correspondence on this dimension is not surprising. 29 On the other hand, the Future Worries dimension is not as accessible or directly observable, since it refers to worries expressed by the child over the future ( e.g ., not being able to drive a car when they grow up).…”
Section: Discussionmentioning
confidence: 95%
“…Also, parents in our study were, on average, in favor of their child playing computer games and sports. Still, the use of a computer has been restricted for pupils with epilepsy in certain British secondary schools [38] because some children and adolescents exhibit photosensitive seizures [39]. With regard to sports, it has been reported that teenagers with higher frequency of seizures participate in fewer sports activities compared with healthy peers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, teachers have a good attitude towards epilepsy, but rely on non‐medical sources of information and would prefer more support from paediatricians (Bannon et al . 1992; Dunkley et al . 2003; Bishop & Boag 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, staff working in mainstream education will need to become more familiar and confident in managing pupils with epilepsy and associated disabilities because of the increasing tendency, in the UK and elsewhere, for children with special educational needs to be supported within mainstream schools (Department for Education and Skills 2001). Generally, teachers have a good attitude towards epilepsy, but rely on non-medical sources of information and would prefer more support from paediatricians (Bannon et al 1992;Dunkley et al 2003;Bishop & Boag 2006).…”
Section: Discussionmentioning
confidence: 99%